Topology Optimization and Structure Partition for Additive Manufacturing: A Literature Review - Xu, Feifei (2016)
With the development of additive manufacturing (AM), the constraints associated with traditional subtractive manufacturing have been largely alleviated. The improved design freedom due to the nature of additive manufacturing, which fabricates objects on a layer-by-layer basis, allows the manufacturing of parts of almost any shape theoretically. Apart from Design for Manufacturing (DMF), a new concept – Design for Additive Manufacturing (DFAM) has been introduced. One promising application arises from DFAM is the light weight structure, which can be achieved by topology optimization (TO). In this paper, two common TO methods will be reviewed. An important issue for applying TO to AM is that the optimized structure may not be simply and directly manufactured using an AM machine due to the constraints of AM technology. One particular constraint is the limited build size of most commercial 3D printers, which requires the part to be partitioned and printed in several parts. This limitation and some part partitioning methods outside TO will also be reviewed in this paper.